The mighty dead : why Homer matters - Nicolson, Adam, 1957- (William Collins, 2014)
Where does Homer come from? And why does Homer matter? His epic poems of war and suffering can still speak to us of the role of destiny in life, of cruelty, of humanity and its frailty, but why they do is a mystery. How can we be so intimate with something so distant?